2008
DOI: 10.1080/13548500701335698
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in chronic fatigue syndrome: Predictors of physical functioning and psychological distress

Abstract: This study investigated health-related quality of life (HRQoL; physical functioning and psychological distress) in an Australian chronic fatigue syndrome (CFS) population. The aims of the study were to compare HRQoL in those with CFS to the normal population, and to investigate the extent to which sociodemographic (age, gender, partner status, education), illness-related (illness duration, symptom frequency), and fatigue severity (physical, mental) variables predicted HRQoL. A total of 139 people meeting CFS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 47 publications
2
29
1
Order By: Relevance
“…Nevertheless, the present results support previous research, which has suggested that in addition to the help of qualified professionals, partners could become a key resource in terms of helping patients cope with CFS (Garralda & Chalder, 2005). More formal strategies are clearly needed for the care of CFS patients not only in terms of physical aspects, by means of pharmacological treatments or physical exercise (Karper & Stasik, 2003;Segar, Eccles, & Richardson, 2008), but also on the emotional and social levels (Friedberg & Sohl, 2009;Jason et al, 2003;Lowry & Pakenham, 2008).…”
Section: Psychology Health and Medicine 159supporting
confidence: 85%
“…Nevertheless, the present results support previous research, which has suggested that in addition to the help of qualified professionals, partners could become a key resource in terms of helping patients cope with CFS (Garralda & Chalder, 2005). More formal strategies are clearly needed for the care of CFS patients not only in terms of physical aspects, by means of pharmacological treatments or physical exercise (Karper & Stasik, 2003;Segar, Eccles, & Richardson, 2008), but also on the emotional and social levels (Friedberg & Sohl, 2009;Jason et al, 2003;Lowry & Pakenham, 2008).…”
Section: Psychology Health and Medicine 159supporting
confidence: 85%
“…With the exception of floor effects reported for the PF domain, the SF-36 had acceptable measurement properties. A single study provided limited evidence in support of the validity of the SF-36 (Version 2), but did not describe the precision of the revised PF domain [112]. Evidence of precision was not found for other generic measures.…”
Section: Generic Assessmentmentioning
confidence: 97%
“…: a viral infection), and for this reason, the syndrome is also called "Chronic Fatigue Immune Dysfunction Syndrome" (CFIDS) (8). CFS is characterised by severe prolonged fatigue, and decreases in cognition and other physiological functions, resulting in severe loss of health-related quality of life (HRQoL) more than that observed in other chronic medical conditions (9)(10). On the other hand, the self-perceived HRQoL of these patients could influence the clinical presentation of the syndrome in a negative way ( II ).…”
mentioning
confidence: 99%